2013
DOI: 10.1074/jbc.m112.449306
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Sorting Nexin 11 (SNX11) Reveals a Novel Extended Phox Homology (PX) Domain Critical for Inhibition of SNX10-induced Vacuolation

Abstract: Background: SNX10 and SNX11 exhibit antagonistic activity in regulating endosome vacuolation. Results: Two additional ␣-helices downstream of the conventional PX domain were identified in the SNX11 crystal structure. Conclusion: SNX11 contains an extended PX (PXe) domain critical for the inhibition of vacuolation induced by SNX10. Significance: This study reports a novel PXe domain that may represent a new subgroup of the PX domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Mutations of Arg16Leu, Tyr32Ser and Arg51Gln/Pro were reported to lead to osteopetrosis. Based on previous sequence alignment studies, Arg16 is specific to SNX10 and conserved between multispecies . Tyr32 is very conserved among SNXs; Arg51 is conserved in the subfamily of SNX10, including SNX3, SNX11, and SNX12 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mutations of Arg16Leu, Tyr32Ser and Arg51Gln/Pro were reported to lead to osteopetrosis. Based on previous sequence alignment studies, Arg16 is specific to SNX10 and conserved between multispecies . Tyr32 is very conserved among SNXs; Arg51 is conserved in the subfamily of SNX10, including SNX3, SNX11, and SNX12 .…”
Section: Resultsmentioning
confidence: 98%
“…In our previous study, we found that the conventional PX domain and a following C‐terminal segment (amino acids 123–153) of SNX10 are necessary for the vacuolation activity of SNX10 . More recently, in our report on the structure of SNX11, the closest paralogue of SNX10, we defined a new PX‐extending domain (PXe) containing the canonical PX domain and two additional α‐helices bundled at the tail . Based on sequence alignment, we speculated that the new PXe domain also existed in SNX10 and was responsible for SNX10 vacuolation activity.…”
Section: Introductionmentioning
confidence: 99%
“…The functional significance of this insertion still remains unclear, but it has been suggested to confer altered membrane binding and remodeling properties to this subset of SNX-BAR proteins (3). Recently, the structure of the SNX11 PX domain was reported to possess a novel extended ␣-helical structure (also present in SNX10), which is required for its regulation of endosomal vacuolization (45).…”
Section: Figure 3 Phosphoinositide Binding By the Px Domains Of The mentioning
confidence: 99%
“…In the case of SNX13 a construct containing the C-terminal RGS, PX, and PXC (50), as well as the structurally divergent PX domain from SNX5, which has a highly extended ␣-helical hairpin insertion following the Pro-rich loop (44), and the SNX11 PX domain shown to possess extended ␣-helical structure at the C terminus important for its function (45). ␤-Strands are indicated in gold, and ␣-helices in blue.…”
Section: Localization Of Snx19 To a Subpopulation Of Endosomes Requirmentioning
confidence: 99%
“…13 Very recently, a related PX-containing protein (SNX11) was shown to inhibit SNX10 vacuole-forming activity, either via direct interaction with SNX10 or via interaction with a common partner. 14 A segment of SNX11 and a segment of SNX10 CD (α4 and α5 in Figure 1) were required to mediate this interaction. The authors propose that SNX11 (and SNX10) contains an ‘extended’ PX domain, including the conventional PX (α1,α2 and α3) plus α4 and α5.…”
Section: Osteopetrotic Mutations In Snx10mentioning
confidence: 99%